The path of violence: Origins, development and outcome of the internal armed conflict in Peru, 1980-1992 - Duche-Pérez, Aleixandre Brian; Vera Revilla, Cintya Yadira; Tomaylla Quispe, Ygnacio Salvador (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
After the years of political violence in the 1980s and early 1990s, Peru was involved in structural changes that allowed a national reconstruction of Peruvian society. During this period, the different migratory processes, changes in internal economic policy, political and educational reforms conditioned Peruvians and future generations under an urban model of development based on consumption, individuality and modernity. A model of political, educational and cultural development that does not include violence and memory as part of national identity and activities. This text proposes a critical look at the origins and consequences of political violence in our country, analyzing the relationship between the actors involved, the ideological projects and the struggle for human rights.